Study of the Effect of Load Variation on Disc Temperature and Braking Efficiency ABS (Anti-lock Braking System) on Yamaha Aerox Matic Motorbike with Road Test Method - Mochammad Rafli Sholehudin Randy; Setya Wijayanta (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
This study aims to analyze the effect of load variation on braking efficiency and disc temperature in Yamaha Aerox automatic motorcycles equipped with an Anti-lock Braking System (ABS) using the roadtest method. The experimental research method was applied, with independent variables including load variations (65 kg, 85 kg, 130 kg, and 150 kg) and two ABS conditions (active and inactive). The dependent variables observed were braking distance, deceleration, braking efficiency, and disc temperature. The research findings indicate that at low speeds (40 km/h), the ABS system results in a longer braking distance compared to non-ABS conditions. However, at high speeds (50 km/h), ABS proves to be more effective in optimizing braking performance and preventing wheel lock, especially under heavier loads. The lowest average value in braking efficiency is obtained in the ABS ON 40 km/h treatment with a load of 150 kg, the result is 51%. while the highest average value of efficiency is obtained in the ABS ON 50 km/h treatment with a load of 65 kg, the result is 92%. Additionally, load variation significantly affects the increase in disc temperature, with heavier loads leading to higher disc temperatures after braking. The lowest average for disc temperature was obtained in the ABS ON 40 km/h treatment with a load of 65 kg, the value is 37.16 degrees Celsius. while the highest average value of disc temperature was obtained in the ABS OFF 50 km/h treatment with a load of 150 kg with an average value of 73.1 degrees Celsius. This study provides valuable insights into the effectiveness of ABS in enhancing road safety and highlights the importance of regulatory considerations regarding the implementation of ABS in motorcycles in Indonesia.